Taking Playful Scholarship Seriously: Discursive Game Design as a Means of Tackling Intractable Controversies - Werning, Stefan; van Vught, Jasper (Eludamos: Journal for Computer Game Culture, 2021)
The article at hand explores the concept of playful scholarship, focusing specifically on the use of playfulness in re-assessing the collaboration between academia and societal partners to tackle “intractable policy controversies” (Schön and Rein 1994, p. 23)—i.e., challenges in which opposing parties operate with conflicting frames (often without even noticing). After arguing that earlier attempts at using games in academia often only evoke the rhetoric rather than the spirit of play (Sicart 2014) and thereby limit spaces for actually playful scholarship, we emphasize how the heuristic of playful game design (rather than game play) can help address this issue. To illustrate our point, we draw on a recent research project about drug policies in the Netherlands, in which concerns of (among others) law enforcement, policy-makers and healthcare workers are characteristically entangled. In this project, we first we defined the societal context of drug policies as an “ecology of games” (Long 1958; Lubell 2013) and proposed two ‘base games’—one created from scratch and the other inspired by the CIA-developed card game Collection Deck. These games were iteratively played by a diverse group of academic and non-academic stakeholders using self-modifying rules that allowed participants themselves to engage in “playful design” (Flanagan 2014), changing, adding or removing rules in order to identify where the game-as-model deviated from their lived experience (and how they might translate their experiences into the ‘language’ of the game). Drawing on ethnographic data collected over the course of six months, we investigate how the contingent ‘versions’ of the game as boundary objects (Leigh Star 2010) facilitated a playful attitude towards the otherwise characteristically entrenched discourse on Dutch drug policies. As a basic frame of reference, we use and adapt Lieberman’s original definition of playfulness, based on “physical, social, and cognitive spontaneity, manifest joy, and sense of humor” (2014, p. 23), and Shen’s differentiation between “situations for play” (2020, p. 540) and “playful states” (2020, p. 542) to interpret the processes in our community of practice. More specifically, we observe the impact of playful objects and object play (Riede et al. 2018) as well as bricolage (Antonijevic and Cahoy 2018) on playful attitudes within the group. This showed the constant tension between, on the one hand, expectations that the game itself should ‘produce’ new insights and, on the other, as Sicart recommends, “carnivalesque” (2014, p. 23) attempts at resisting ‘utilitarian’ play (e.g., exploring ideas that would be ruled out by conventional wisdom as optional in-game scenarios or events). Finally, we conclude with how adopting a playful game designer’s rather than a player’s perspective may challenge habitualized practices and corresponding roles inherent in public-private partnerships within academia. This makes different preconceptions amongst stakeholders visible, facilitates perspective change, and acknowledges the interconnected frames within intractable controversies by continually re-designing the base games.